2015
DOI: 10.1021/acs.langmuir.5b01649
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Colloidal Particles in the Presence of Multivalent Co-Ions: The Inverse Schulze–Hardy Rule

Abstract: Shifts of the critical coagulation concentration (CCC) in particle suspensions in salt solutions containing multivalent co-ions and monovalent counterions are rationalized. One observes that the CCC is inversely proportional to the valence, and this behavior is referred to as the inverse Schulze-Hardy rule. This dependence is established by means of measurements of the stability ratio for positively and negatively charged latex particles with time-resolved light scattering. The same dependence is equally sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
63
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 28 publications
(72 reference statements)
7
63
1
Order By: Relevance
“…For a 1:2 electrolyte the effect is weaker, but noticeable, similarly to the difference between the Monte Carlo data and the DLVO curve in [14]. The greater reduction of the electrostatic repulsion with the rise of coion valence found in the present study is in qualitative agreement with the inverse Schulze-Hardy rule established in [37]. …”
Section: Materials Methods and Experimental Resultssupporting
confidence: 90%
“…For a 1:2 electrolyte the effect is weaker, but noticeable, similarly to the difference between the Monte Carlo data and the DLVO curve in [14]. The greater reduction of the electrostatic repulsion with the rise of coion valence found in the present study is in qualitative agreement with the inverse Schulze-Hardy rule established in [37]. …”
Section: Materials Methods and Experimental Resultssupporting
confidence: 90%
“…coagulating power of coions decreases with increasing valence. Due to this inversion, the phenomenon was given a name: inverse Schulze-Hardy rule [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Trefalt et al [13][14][15][16][17][18][19] have recently investigated the critical coagulation concentration of charged colloids in electrolyte solutions with 1:Z ions (monovalent counterion and multivalent co-ion) and have reported that aggregation behavior depends on the co-ion valence, even though the ionic strengths are the same. Though a similar behavior, i.e., more effective aggregation with smaller co-ion valence, has been reported for the coil-globule transition of DNA [20,21], there have been only a few reports on colloidal aggregation in electrolyte solutions with 1:Z ions.…”
mentioning
confidence: 99%